Emotional intelligence as a mediator in the relationship between academic performance and burnout in high school students - Molero Jurado, María del Mar (PLoS One, 2021)
Low performance of high school students and repeating a year are major problems in the education system. Low performance in the classroom generates negative emotions in young people and has been related to development of school burnout. The objective of this study was to analyze the repercussions of academic performance on burnout in high school students, and establish the role of emotional intelligence in this relationship. The sample was made up of 1287 high school students aged 14 to 18, who filled out questionnaires for evaluation of these variables. The results showed that youths who had failed a subject or had repeated a year showed more exhaustion and cynicism than their classmates with better performance and higher academic efficacy. A relationship was also found between school burnout and emotional intelligence in these adolescents, positive for self-efficacy and negative for cynicism and exhaustion. The model results showed that low academic performance affected burnout level, and that stress management and mood in emotional intelligence acted as a mediator in this relationship. In conclusion, development of emotional intelligence programs in the educational context is proposed as a measure for preventing burnout in the face of adverse high school academic events, such as failing or repeating a year.